Replanting, Purification, and Preservation of Cercospora - Dian Eka Kusumawati; Istiqomah Istiqomah (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2017)
Cercospora is a group of Ascomycota fungi undergo meiosis after zygote formation of the short-lived and produce meiospora with the formation of free cells in a meiosporagium called ascus. Ascomycota indicates sexual compatibility bipolar and have cell walls composed of two layers (bi-layered). Phylogenetic tree based on 18S rDNA sequences showed that the Ascomycota and Basidiomycota have divergence from one another in the Paleozoic era, about 500 million years ago. Cercospora fungus is also a fungus that can cause disease is quite common in plants. In culturing the fungus cercospora there are some processes that do the replanting, purification and preservation. Replanting isolate of the fungus Cercospora replanting which is the work of moving the fungus Cercospora isolates from the old medium into a new medium with a very high level of accuracy. In this case replanting process is done by using the method of puncture. Purification is a process of purifying the fungus Cercospora isolates from other microorganisms (fungi and bacteria) who participated grow during the isolation process, usually done by taking the hyphae at the very end of the isolates. Preservation is the storage and maintenance activities of the fungus Cercospora isolates using glycerol solution which will then be stored in the refrigerator in a certain period.